The quality of licensing services: an analysis of the impact of leadership and communication on the effectiveness of licensing services in Indonesia - Rachmat, Rachmat (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The establishment of the Public Service Mall in XYZ Regency is designed to facilitate business transactions and is anticipated to enhance the Ease of Doing Business Index (EoDB) in XYZ Regency. The Investment Coordinating Board (BKPM) has delegated authority to the XYZ Regency Investment and One-Stop Integrated Services Office or it called DPMPTSP to organize licensing in the XYZ region through the Public Service Mall. The government utilizes an integrated online system, namely Online Single Submission (OSS), in its implementation, as mandated by Government Regulation Number 24 of 2018 concerning Electronically Integrated Business Licensing Services. This is done by the government to accelerate and facilitate business actors in obtaining business licenses. XYZ Regency has implemented the OSS system since July 2018. In this study, the authors are interested in discussing how communication management and communication processes related to services carried out by the XYZ Regency Investment and One-Stop Integrated Services Office (DPMPTSP) are conducted. The methodology employed in this study is descriptive qualitative. In accordance with the POAC theory, the implementation of the OSS system at the XYZ Regency One-Stop Integrated Investment and Service Office has not achieved the desired outcomes. There remain numerous deficiencies in the system, starting with the readiness of human resources (HR) to provide optimal services and the strategy of the XYZ Regency local government to disseminate information on the OSS system to the wider community. In accordance with the explanation provided by G. R. Terry, the foundation of management activities is organization. This implies that organization is an activity aimed at achieving goals in an effective and efficient manner. Therefore, the objective of the OSS system should be genuinely perceived by the community, rather than becoming an impediment to business activities.